Dunbar syndrome: celiac trunk compression - Praderi, Raúl C; Pereyra Borrelli, César (Cirugía del Uruguay, 1973)
A 66 years-old patient, with such acute epigastric pain that he had to be treated with strong analgesics, was exhaustively studied, but no explanation to his pain was found. It was not possible to perform selective angiography of celiac trunk by reason of highly sinous iliacs and aorta. Nor were profile aortographies, possible. No visceral lesions were found during surgery, but an important fremitus of hepatic artery was discovered. Celiac trunk was liberated at leve! of the aortic ring. Fremitus disappeared during surgery and pain during post-operatory period. The case was classified as Dunbar's syndrome.